2021
DOI: 10.48550/arxiv.2103.14450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solution of Disordered Microphases in the Bethe approximation

Patrick Charbonneau,
Marco Tarzia

Abstract: The periodic microphases that self-assemble in systems with competing short-range attractive and long-range repulsive interactions are structurally both rich and elegant. Significant theoretical and computational efforts have thus been dedicated to untangling their properties. By contrast, disordered microphases, which are structurally just as rich but nowhere near as elegant, have not been as carefully considered. Part of the difficulty is that simple mean-field descriptions make a homogeneity assumption that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…(Reference 18 concluded that a continuous transition takes place for κ = 0.48, based on the absence of discontinuity in u(T ), but did not consider the weakly first-order transition scenario.) Interestingly, a recent computation for a low-connectivity Bethe lattice suggests that such a weakly first-order transition in the vicinity of the multicritical point (κ < ∼ 1/2 in the DNNI model) is a mean-field feature [48]. This behavior thus clearly differs from the fluctuation-induced discontinuity of the weakly first-order transition for 1/2 < κ < κ * .…”
Section: For An Ashkin-teller (At)-type Phase Transitionmentioning
confidence: 92%
“…(Reference 18 concluded that a continuous transition takes place for κ = 0.48, based on the absence of discontinuity in u(T ), but did not consider the weakly first-order transition scenario.) Interestingly, a recent computation for a low-connectivity Bethe lattice suggests that such a weakly first-order transition in the vicinity of the multicritical point (κ < ∼ 1/2 in the DNNI model) is a mean-field feature [48]. This behavior thus clearly differs from the fluctuation-induced discontinuity of the weakly first-order transition for 1/2 < κ < κ * .…”
Section: For An Ashkin-teller (At)-type Phase Transitionmentioning
confidence: 92%